Epidural anesthesia with ropivacaine with or without clonidine and postoperative pain in hemorrhoidectomies - Baptista,João Florêncio de Abreu (2014)
PURPOSE: To determine the safety, pain intensity correlated with age and body mass index (BMI), epidural anesthesia with ropivacaine and clonidine in hemorrhoidectomy.METHODS: Eighty patients, both genders, 20-70 years old, ASA I or II, for hemorrhoidectomy were randomly divided into two groups: Control (n=38), epidural anesthesia with 14 mL of ropivacaine 0.75 % plus 0.0266 mL/kg of 0.9% saline solution; Experimental (n=42) epidural anesthesia with 14 mL of 0.75% ropivacaine plus 4.0 mcg/kg of clonidine. In preoperative and postoperative period were evaluated: systolic blood pressure (SBP), diastolic blood pressure (DBP ), heart rate (HR ), pulse oximetry (SpO2), electrocardiography (ECG), pain intensity (VAS ) in four, eight and, 12 hours and analgesic consumption.RESULTS: The VAS values differed between four, eight and 12 hours in the Experimental Group, where correlation of VAS 12h with age (p<0.05) occurred and not with BMI and more patients (p<0.05) did not receive analgesics. SBP, DBP, HR changed similarly in both groups at 15, 30 and 45 min. The ECG and SpO2 remained unchanged.CONCLUSIONS: Clonidine (4mcg/kg) in epidural anesthesia with ropivacaine 0.75% in hemorrhoidectomy showed safety and greater analgesia within four hours. The pain at 12 hours showed correlation with age and not with body mass index.